Vegetable oil as a highly effective 100% bio-based alternative solvent for the one-pot multicomponent Biginelli reaction. Issue 16 (28th June 2021) - Noppawan, Pakin; Sangon, Suwiwat; Supanchaiyamat, Nontipa; Hunt, Andrew J.
Abstract : Multicomponent one-pot Biginelli reactions have been successfully performed using vegetable oil as bio-based, non-toxic, and environmentally friendly solvents. Abstract : Multicomponent one-pot Biginelli reactions have been successfully performed using vegetable oil as bio-based, non-toxic, and environmentally friendly solvents. Palm oil was demonstrated to be a highly effective greener solvent as compared to petroleum-based solvents such as cyclohexane, with comparable yields for the Biginelli reaction of urea, benzaldehyde, and methyl 3-oxobutanoate, of 74% and 73%, respectively. Moreover, palm oil was easily recovered from the reaction mixture and reused for at least 4 additional reactions with a consistent yield of 60%, which was in stark contrast with cyclohexane that was unable to recovered and reused in this reaction. Virgin palm oil exhibited clear solvent effects including enhanced solubility of substrates and promotion of the keto–enol tautomerisation leading to an increased reaction productivity when compared to previous published bio-based solvents such as p -cymene and ethyl lactate. Green metrics evaluation using process mass intensity (PMI), E-factor, solvent intensity (SI), and water intensity (WI) for the Biginelli reaction using palm oil was found to be more sustainable and safer than cyclohexane, p -cymene and ethyl lactate. Moreover, waste palm oil could be utilised with comparable yields to p -cymene and ethyl lactate, but importantly has a lower associated environmental impact. If sustainably sourced, vegetable oils can create new opportunities for chemists to improve the green credentials of multicomponent reactions with a safer and cheaper renewable alternative to petroleum derived solvents.